2001
DOI: 10.3130/aijs.66.17_2
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Rate and Strength Development of Cementitious Material Under Freezing or Dry Condition

Abstract: We investigated hydration and strength developrnent of cementitious materials cured under freezing or drying condi ・ tion experimentall γ The test results show that hydration and stren 匹 h development depend onboth tenΨ erature and chemical potential ofwater . Theoretical study makes it clear that e飩 ct oftemperature fblows the Arrhenius equation and the activation energy in the equation is proportion 湿 to the decrease of chemical potentia1 . Consequently the equivalent maturity method that describes the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The strength development of concrete is highly contingent on the hydration reaction of cement and water. The temperature dependence of the hydration reaction rate is expressed in terms of the equivalent age with the Arrhenius equation [15]. The chemical potential of water deteriorates significantly under drying and freezing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength development of concrete is highly contingent on the hydration reaction of cement and water. The temperature dependence of the hydration reaction rate is expressed in terms of the equivalent age with the Arrhenius equation [15]. The chemical potential of water deteriorates significantly under drying and freezing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the reaction rate of hardened cement paste in a drying or freezing environment decreased owing to a decrease in the chemical potential of the water reacting with the cement. This decrease was expressed as follows by incorporating the decrease in the chemical potential of water into the Arrhenius equation [15,16]. k T = A exp(− E + αμ / RT ) where k T denotes the reaction rate integer at temperature T (K); A and α denote experiment integer; E denotes apparent activation energy (J/mol); μ denotes the chemical potential of water (J/mol); R denotes the gas constant (J/mol·K).…”
Section: Resultsmentioning
confidence: 99%